2018
DOI: 10.1097/ccm.0000000000003192
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Transfusion Practices in Critically Ill Children

Abstract: The majority of platelet transfusions are given as prophylaxis to nonbleeding children, and significant variation in platelet thresholds exists. Studies are needed to clarify appropriate indications, with focus on prophylactic transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 15 publications
4
77
1
Order By: Relevance
“…Another reason is that most patients who are transfused with PC are immunocompromised and thus vulnerable to bacterial infection. 1,2 Significant numbers of septic reactions and fatal outcomes related to PC transfusion have been reported from many countries. [3][4][5][6] Various interventions to mitigate these consequences of PC transfusion have been proposed, as follows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason is that most patients who are transfused with PC are immunocompromised and thus vulnerable to bacterial infection. 1,2 Significant numbers of septic reactions and fatal outcomes related to PC transfusion have been reported from many countries. [3][4][5][6] Various interventions to mitigate these consequences of PC transfusion have been proposed, as follows.…”
Section: Discussionmentioning
confidence: 99%
“…The major reason for this compared with red cell or plasma components is a high bacterial load derived from storing PC at 20‐24°C, which enables vigorous bacterial proliferation in PC during the preservation process. Another reason is that most patients who are transfused with PC are immunocompromised and thus vulnerable to bacterial infection . Significant numbers of septic reactions and fatal outcomes related to PC transfusion have been reported from many countries …”
mentioning
confidence: 99%
“…In critically ill children, the most common reason platelets are given is prophylaxis for bleeding risk in patients with thrombocytopenia. In the same studies, platelet transfusions are associated with increased mortality 143,144 . In a review of 511 children on ECMO, Cashen et al 145 found that 97.1% were transfused platelets during the course of their ECMO run.…”
Section: Transfusion Thresholdsmentioning
confidence: 99%
“…In addition, during 57% (8/14) of the admissions, patients experienced bleeding; 63%(5/8) of the time, the bleeding was significant. During these PTR events, the median platelet threshold prior to transfusions was 18 × 10 9 /L (IQR:[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], and the median posttransfusion increment was 3 × 10 9 /L (IQR: 1-6). These children typically received platelets stored for a median of 4 days (IQR: 3-5 days) that were ABO matched (67%; 50/74) and apheresis products (53%; 39/74).…”
mentioning
confidence: 99%